Paradojas de la modernidad - BRUNET, Graciela (UNIVERSIDAD NACIONAL DEL LITORAL, 2000)
Otros descriptores: TERCER REICH; ILUSTRACION; POSMODERNIDAD; HITLER, Adolfo; NIETZSCHE; HEIDEGGER; WEIMAR; LONG, F.; JUNGER, Ernst